Hubungan Dukungan Keluarga Dengan Diabetes Self Management pada Pasien Diabetes Mellitus Tipe II di Rumah Sakit Mitra Medika - Afina Muharani Syaftriani; Maria Haryanti Butar-butar; Sri Lasmawanti; Yuniati Yuniati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Diabetes Mellitus (DM) is a chronic disease that is seen from signs of the body's inability to metabolize carbohydrates, fats and proteins optimally, causing hyperglycemia (high blood glucose levels). An aspect that can improve self-management of Type II DM patients is family support. The family is a component that influences Type II DM sufferers in supporting patients to fulfill self-management. The aim of this research is to determine the relationship between family support for diabetes self-management in Type II Diabetes Mellitus sufferers at Mitra Medika Hospital. This research design uses an analytical survey method with a cross-sectional approach. The research population was 720 respondents, the research sample was 88 respondents. Sampling Purposive sampling. With the Slovin formula. Based on the results of the Chi-Square test, the family support test gets a p-value (0.003 < 0.05). So it can be concluded that there is a significant relationship between family support for diabetes self-management in Type II DM patients at Mitra Medika Hospital. The conclusion of this study shows that there is a statistically significant relationship between family support and diabetes self-management in Type II DM patients at Mitra Medika Hospital. Suggestions for Mitra Medika Hospital to improve the quality of service and provide better education for Diabetes Mellitus sufferers.